2016
DOI: 10.1111/1475-6773.12446
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of National Guard Mental Health Service Utilization in VA versus Non‐VA Settings

Abstract: Objective. To determine associations between need, enabling, and predisposing factors with mental health service use among National Guard soldiers in the first year following a combat deployment to Iraq or Afghanistan. Data Sources/Study Setting. Primary data were collected between 2011 and 2013 from 1,426 Guard soldiers representing 36 units. Study Design. Associations between Guard soldier factors and any mental health service use were assessed using multivariable logistic regression models in a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Our findings indicate that even after adjusting for many covariates, including several need-related proxies, ResF personnel’s overall MHSU was 61%; approximately, 11% lower relative to RegF. Others have found that even when controlling for need, MHSU among ResF personnel tends to be lower 12 18 19 39. For example, one US study that assessed a sample of National Guard and Reserve personnel who returned from deployments to Iraq or Afghanistan between 2006 and 2009 identified 60% with a need for mental health services yet only 50% of these individuals reported accessing care in the 12 months following deployment return 39.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our findings indicate that even after adjusting for many covariates, including several need-related proxies, ResF personnel’s overall MHSU was 61%; approximately, 11% lower relative to RegF. Others have found that even when controlling for need, MHSU among ResF personnel tends to be lower 12 18 19 39. For example, one US study that assessed a sample of National Guard and Reserve personnel who returned from deployments to Iraq or Afghanistan between 2006 and 2009 identified 60% with a need for mental health services yet only 50% of these individuals reported accessing care in the 12 months following deployment return 39.…”
Section: Discussionmentioning
confidence: 64%
“…Our analyses were among personnel with a mental disorder, that is, those who would presumably benefit from MHSU and, ideally, perceive a need for these services. Other researchers have observed that need18 19 and psychiatric distress39 largely predict MHSU but this appears to be only one of many influencing factors. Our findings indicate that even after adjusting for many covariates, including several need-related proxies, ResF personnel’s overall MHSU was 61%; approximately, 11% lower relative to RegF.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We found moderate strength of evidence indicating no or very small differences in the proportion of engaged and non-engaged Veterans who reside in rural areas. Articles including engaged and non-engaged Veterans also employed varying measures of rurality, including MSA, 21,55,138 self-reported rural/urban residence, 70,107,120 RUC codes, 81,137 Rural-Urban Commuting Area (RUCA) codes, 26,47,48 and straight-line distances between participant homes and nearest VHA facility 98 (online Appendix Table 6). More than half of articles reported no difference in rural residence between engaged and non-engaged Veterans (actual estimates 6-26%).…”
Section: Ruralitymentioning
confidence: 99%
“…More than half of articles reported no difference in rural residence between engaged and non-engaged Veterans (actual estimates 6-26%). 47,48,55,70,73,107,120,138 One medium-quality article found slightly higher rurality for engaged Veterans (30 vs 24% of non-engaged). 137 In contrast, another medium-quality article reported lower rural residence in engaged Veterans (18% engaged vs 28% non-engaged), but was limited to Native Americans enrolled in VHA and Indian Health Service.…”
Section: Ruralitymentioning
confidence: 99%